Evaluasi Pelayanan Kartu Tanda Penduduk Di Mal Pelayanan Publik (MPP) Kabupaten Sidoarjo - Syarifatul Mufarrijah; Alfentira Mega Sasikaraya; Rizka Adha Khairunnisa; Singgih Manggalou (Jurnal Ilmu Administrasi Negara, 2025)
This study aims to evaluate the service quality of Identity Card (KTP) issuance at the Public Service Mal (MPP) in Sidoarjo Regency, which remains a center for population administration services but still faces challenges in completing KTP applications submitted by the community. This study uses a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that the KTP service process at the MPP in Sidoarjo is still suboptimal. This is evidenced by several obstacles caused by insufficient service facilities such as waiting areas, limited KTP blank forms, long waiting times, and uncertainty in KTP collection. Furthermore, the lack of socialization related to digital service like Plavon also affects service effectiveness. These challenges reflect gaps in aspects of adequacy, efficiency, and responsiveness of the service. Keywords: Evaluation, Service, Idetity Card (KTP).